On face antimagic labelings of disjoint union of prisms - Ali, Gohar; Bača, Martin; Bashir, Fozia; Feňovčíková, Andrea Semaničová (Utilitas Mathematica, 2011)
We deal with the problem of labeling the vertices, edges and faces of a plane graph in such a way that the label of a face and the labels of the vertices and edges surrounding that face add up to a weight of that face and the weights of all s-sided faces constitute an arithmetic progression of difference d. In this paper, we describe various antimagic labelings for the disjoint union of prisms.